Pendeteksian kecurangan laporan keuangan dengan menggunakan model beneish m-score: perspektif fraud diamond - Andy Dharma Pangestu; Reni Oktavia; Yunia Amelia (Penerbit Goodwood, 2020)
Purpose: This study aims to prove whether pressure, opportunity, rationalization and capability elements of fraud diamond theory related to financial statements fraud. Research methodology: This associative research uses quantitative data with sources from company website and the Indonesia Stock Exchange (IDX). 55 companies listed in the infrastructure, utility and transportation sectors on the IDX during the 2016-2018 period used as the population in this research, with a total of 153 observations as sample. This research used logistic regression with IBM SPSS Statistics 26 program. Results: This research shows that only financial stability has positive effect on risk of commiting fraud, while the variables of natures of industry, rationalization and capability have no association with the financial statement fraud. Limitations: The measurement of the dependent variable uses Beneish M-Score, a probability model, therefore it is not 100% accurate; it is limited to the sector and period under study; and the low coefficient of determination in this study. Contribution: Providing empirical evidence about factors that support the occurrence of commiting fraud which will help investor and financial service authority. Keywords: Fraud, Fraud Diamond, Financial Statement, Beneish M-Score